Managing the almond and stone fruit replant disease complex with less soil fumigant - Greg Browne; Bruce Lampinen; Brent Holtz; David Doll; Shrinivasa Upadhyaya; Leigh S. Schmidt; Ravindra G. Bhat; Vasu Udompetaikul; Robert W. Coates; Bradley D. Hanson; Karen Klonsky; Suduan Gao; et al. (My University, 2013)
As much as one-third of California's almond and stone fruit acreage is infested with potentially debilitating plant parasitic nematodes, and even more of the land is impacted by Prunus replant disease (PRD), a poorly understood soilborne disease complex that suppresses early growth and cumulative yield in replanted almond and peach orchards. Preplant soil fumigation has controlled these key replant problems, but the traditional fumigant of choice, methyl bromide, has been phased out, and other soil fumigants are increasingly regulated and expensive. We tested fumigant and nonfumigant alternatives to methyl bromide in multiple-year replant trials. Costs and benefits were evaluated for alternative fumigants applied by shanks in conventional strip and full-coverage treatments and applied by shanks or drip in novel spot treatments that targeted tree planting sites. Short-term sudangrass rotation and prudent rootstock selection were examined as nonfumigant approaches to managing PRD. Trial results indicated that integrations of the treatments may acceptably control PRD with relatively little soil fumigant.
Keywords: Crop Rotation; Plant Disease Management Techniques